Reorganisasi karang taruna (studi kasus karang taruna “Tunas Kahuripan” Desa Ciela, Kecamatan Bayongbong, Kabupaten Garut) - Aris Tristanto; Yunilisiah Yunilisiah (University of Muhammadiyah Malang, 2022)
Karang taruna is a social organization that ideally can embody social welfare efforts in the midst of society. But in reality, most of the youth organizations’ performances in Indonesia are different than expected, one of which is the